Analysis of computational and critical thinking skills in elementary school science students - Kumala, Farida Nur; Dwi Yasa, Arnelia; Hakim, Arief Rahman; Salimi, Moh. (Jurnal Bidang Pendidikan Dasar, 2025)
This study aims to analyze the computational thinking skills of elementary school students. This research approach uses a qualitative and quantitative descriptive approach. The subjects of the study involved 70 fifth grade students at an elementary school in Malang City. The research instruments were in the form of observation sheets and tests, the data obtained were analyzed qualitatively and quantitatively. The results of the analysis of critical and computational thinking of elementary school students showed that computational thinking skills were still lacking, 35.4% and 54% for critical thinking. The recommendation from the research results is to make it a habit for elementary school students to continue practicing high-level thinking skills through the learning process and the use of learning devices based on high-level thinking skills.